Productive resources & rural women empowerment - Tikaniya, Tripta; Mehta, Sudershan 1957- (Delhi, India : Swastik, 2009)
Study conducted at Rewari, Hisar and Fatehabad districts of Haryana, India.
Includes bibliographical references (p. [139]-150) and index
Keywords: Women in economic development -- India -- Haryana; Gender mainstreaming -- India -- Haryana; Rural women -- India -- Haryana -- Economic conditions